Effects of processing methods on the chemical composition and antioxidant capacity of walnut (Juglans regia L.) oil - Gao, Pan; Liu, Ruijie; Jin, Qingzhe; Wang, Xingguo (Food science & technology, 2021)
Various methods for the processing of walnut oil (cold pressing, roasting pressing, hexane extraction, subcritical butane extraction and supercritical carbon dioxide extraction) were compared, and hexane extraction was shown to provide for efficient lipid isolation. Among the investigated samples, roast-pressed and hexane-extracted oils exhibited the highest C18:1n-9 contents (18.74 and 18.52%, respectively), however featured the lowest C18:2n-6 (63.06 and 62.95%, respectively) and trilinolein (32.82 and 32.06%, respectively) contents. Moreover, the tocopherol (371.08 mg/kg) and the phytosterol (1206.30 mg/kg) content of subcritical butane-extracted walnut oil, the polyphenol content of hexane-extracted oil (45.43 mg/kg), and the squalene content of roast-pressed walnut oil (14.19 mg/kg) exceeded those of other samples. Multiple linear regression analysis was employed to evaluate the contributions of oil constituents to overall antioxidant capacity (oxidative stability and free radical scavenging capacity) and thus establish the corresponding numerical model. It was shown that C16:0, polyphenol, Δ5-avenasterol, SOS, γ-tocopherol, PLL, C18:3n-3, LLL, and C18:0 contributed to the antioxidant capacity of the walnut oil. Overall, the obtained results pave the way to the development of industrial-scale methods of high-quality and high-nutritional-value walnut oil production. •Effects of processing on the composition and properties of walnut oil were probed.•The virtue of walnut oils indicated by chemometrics approaches.•C16:0 and polyphenol were important index for antioxidant capacity prediction of walnut oil.